2015
DOI: 10.1097/jnn.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Home-Based Speed of Processing Training Program in Middle-Aged and Older Adults With HIV

Abstract: There has been much optimism over the positive impact of cART on life expectancy for people with HIV; however, those aging with HIV fear potential day-to-day challenges associated with the development of cognitive deficits. The presence of cognitive deficits has generated major safety concerns as it has been shown to impact driving, mobility, and employment. Given the efficacy of a computerized speed of processing training program administered in the laboratory to older adults and adults with HIV, this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Another study examined a cognitive stimulant program in a sample of 60 participants (with and without HIV infection) and found that neurocognitive function improved for participants who used the program the most (Becker et al, 2012). Two other studies using speed of processing training in middle-aged and older adults with HIV also showed promising effects of training on neurocognitive outcomes (Cody et al, 2015; Vance et al, 2012). Our study is the first to focus on working memory, a core cognitive function that is important for daily living.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study examined a cognitive stimulant program in a sample of 60 participants (with and without HIV infection) and found that neurocognitive function improved for participants who used the program the most (Becker et al, 2012). Two other studies using speed of processing training in middle-aged and older adults with HIV also showed promising effects of training on neurocognitive outcomes (Cody et al, 2015; Vance et al, 2012). Our study is the first to focus on working memory, a core cognitive function that is important for daily living.…”
Section: Discussionmentioning
confidence: 93%
“…While some pilot work has been done (Becker et al, 2012; Boivin et al, 2010; Cody, Fazeli, & Vance, 2015; Vance, Fazeli, Ross, Wadley, & Ball, 2012), the potential for cognitive training to mitigate deficits found in HIV-associated NCI remains understudied. Cognitive training is a promising low-cost intervention that harnesses the brain’s neuroplastic capabilities.…”
mentioning
confidence: 99%
“…Although the ACTIVE study was conducted in healthy older adults, its findings have led investigators to examine the use of computer-based cognitive training in other populations. These populations have included, but are not limited to, people with HIV (Cody, Fazeli, & Vance, 2015;Vance, Fazeli, Ross, Wadley, & Ball, 2012), stroke survivors (Park & Park, 2015;Yoo, Yong, Chung, & Yang, 2015), childhood cancer survivors (Conklin et al, 2015;Hardy, Willard, & Bonner, 2011), and BCS (Kesler et al, 2013;Von Ah et al, 2012). However, this article will focus on computer-based cognitive training interventions tested in BCS.…”
Section: Healthy Older Adults and Computer-based Cognitive Trainingmentioning
confidence: 99%
“…Study design. Among the 24 studies reviewed, there were nine double blind, randomized controlled trials [24, 26-28, 45, 46, 48, 51, 52], one randomized waitlist controlled trial study [53], one multicenter randomized control trial [29], three pilot studies [47,54,55], one single group study [49], one within subject study [56], one controlled experimental design [57], one follow-up single group design study [58], one case control study [59], one longitudinal within-…”
Section: Remote Cognitive Remediation and Cognitive Training Researchmentioning
confidence: 99%
“…Of the 24 studies examined, seven studies utilized principles of cognitive remediation [28,29,44,48,58,60,61], whereas the other 17 studies utilized cognitive training exclusively. Participants completed tasks individually (n = 14/24 studies) [24,26,44,45,48,49,51,52,[54][55][56][57][58][59], or with a partner (n = 10/24 studies) [27-29, 43, 46, 47, 50, 53, 60, 61]. Studies used printed materials (n = 7/24 studies) [27-29, 48, 50, 60, 61] and internet-based and/or computer-based programs (n = 18/24 studies) [24, 26, 43-49, 51, 59] to deliver the intervention to participants.…”
Section: Remote Cognitive Remediation and Cognitive Training Researchmentioning
confidence: 99%